Marijuana : a reference handbook - Newton, David E. (Contemporary world issues., 2017)
This book examines the production, consumption, and regulation of the Cannabis plant; the plant's commercial, recreational, medicinal, and religious applications; and the various attempts to regulate the production and consumption of marijuana in the United States and other parts of the world. Additionally, it provides a detailed history of the role of marijuana in society, and presents arguments for and against its legalization or decriminalization.